The function of probiotics on the treatment of ventilator‐associated pneumonia (VAP): facts and gaps. Issue 9 (September 2017) - Karacaer, Feride; Hamed, Imen; Özogul, Fatih; Glew, Robert H.; Özcengiz, Dilek
Abstract : Abstract : Probiotics have been used for centuries in making fermented dairy products. The health benefits related to probiotics consumption are well recognized and they are generally regarded as safe (GRAS). Their therapeutic effects are due to the production of a variety of antimicrobial compounds, such as short‐chain fatty acids, organic acids (such as lactic, acetic, formic, propionic and butyric acids), ethanol, hydrogen peroxide and bacteriocins. Ventilator‐associated pneumonia (VAP) is a nosocomial infection associated with high mortality in intensive care units. VAP can result from endotracheal intubation and mechanical ventilation. These interventions increase the risk of infection as patients lose the natural barrier between the oropharynx and the trachea, which in turn facilitates the entry of pathogens through the aspiration of oropharyngeal secretions containing bacteria into the lung. In order to prevent this, probiotics have been used extensively against VAP. This review is an update containing information extracted from recent studies on the use of probiotics to treat VAP. In addition, probiotic safety, the therapeutic properties of probiotics, the probiotic strains used and the action of the probiotics mechanism are reviewed. Furthermore, the therapeutic effects of probiotic treatment procedures for VAP are compared to those of antibiotics. Finally, the influences of bacteriocin on the growth of human pathogens, and the side‐effects and limitations of using probiotics for the treatment of VAP are addressed.